PENGARUH KOMPETENSI KERJA DAN MASA KERJA TERHADAP PENGEMBANGAN KARIR KARYAWAN PADA PT. SOCFINDO BANGUN BANDAR DOLOK MASIHUL SERDANG BEDAGAI - Linda Feronika Simanjuntak; Muhammad Asnawi; Al Firah (Universitas Dharmawangsa, 2023)
Â Work competence and tenure is a very important issue in the field of human resources related to improving the career development of employees at the company. Based on the fact that an employee/employee will need a series of knowledge, skills and abilities that are developed to work well and successfully in positions encountered during his career, then career development is an important thing to do to change the human resources of an organization, from a situation to another better state through long-term education and experiential learning in preparing employees for future responsibilities. Career development aims to produce organizational human resources that are reliable and have competencies according to the needs of the organization. The purpose of this study was to determine and analyze the effect of work competence and tenure on employee career development at PT. Socfindo Builds DolokMasihul Port, Serdang Bedagai Regency. The data analysis technique is multiple linear regression analysis. The sample studied was 85 people. The results of the regression analysis obtained a tcount value of 4.943 >ttable 1.663 so it can be concluded that Ho is rejected and H1 is accepted, which means that work competence has a significant influence on employee career development. The results of the regression analysis obtained tcount of 3.828 >ttable 1.663, it can be concluded that Ho is rejected and H2 is accepted, which means that tenure has a significant influence on employee career development. The Fcount value is 49.656 >Ftable 2.37, so it can be concluded that the variables of work competency (X1) and years of service (X2) simultaneously (together) affect the career development variable (Y).Â Keywords : Work Competency, Tenure, Career DevelopmentÂ